Tailoring the electrochemical activity of magnesium chromium oxide towards Mg batteries through control of size and crystal structure. Issue 2 (19th December 2018) - Hu, Linhua; Johnson, Ian D.; Kim, Soojeong; Nolis, Gene M.; Freeland, John W.; Yoo, Hyun Deog; Fister, Timothy T.; McCafferty, Liam; Ashton, Thomas E.; Darr, Jawwad A.; Cabana, Jordi
Abstract : Reversible Mg removal from MgCr2 O4 (a high-voltage Mg-intercalation cathode material) was improved by nanosizing and introducing significant structural defects. Abstract : Chromium oxides with the spinel structure have been predicted to be promising high voltage cathode materials in magnesium batteries. Perennial challenges involving the mobility of Mg 2+ and reaction kinetics can be circumvented by nano-sizing the materials in order to reduce diffusion distances, and by using elevated temperatures to overcome activation energy barriers. Herein, ordered 7 nm crystals of spinel-type MgCr2 O4 were synthesized by a conventional batch hydrothermal method. In comparison, the relatively underexplored Continuous Hydrothermal Flow Synthesis (CHFS) method was used to make highly defective sub-5 nm MgCr2 O4 crystals. When these materials were made into electrodes, they were shown to possess markedly different electrochemical behavior in a Mg 2+ ionic liquid electrolyte, at moderate temperature (110 °C). The anodic activity of the ordered nanocrystals was attributed to surface reactions, most likely involving the electrolyte. In contrast, evidence was gathered regarding the reversible bulk deintercalation of Mg 2+ from the nanocrystals made by CHFS. This work highlights the impact on electrochemical behavior of a precise control of size and crystal structure of MgCr2 O4 . It advances the understanding and design of new cathode materials for Mg-based batteries.